PROJETO EDUCA SERE III - A CARTA IMAGEM DE SÃO JOSÉ DOS CAMPOS - Tania Maria Sausen; Bernardo T. Ruddorff; João Ávila; Romeu Simi Filho; Wellington Rodolfo Castilho de Almeida; Viviane Gomes C. da Rosa; Joaquim Godoi Filho (Boletim de Geografia, 2011)
<>